2020
DOI: 10.1002/jper.20-0613
|View full text |Cite
|
Sign up to set email alerts
|

Association of hyaluronic acid with a deproteinized bovine graft improves bone repair and increases bone formation in critical‐size bone defects

Abstract: Background: This study is designed to evaluate the potential of different formulations of hyaluronic acid (HA) to improve new bone formation in critical-size calvaria defect (CSD) when combined with a deproteinized bovine graft (DBG) material. Methods: Thirty male rats were used. A 5-mm-diameter CSD was created and three experimental groups (n = 10) were randomly assigned based on the treatments performed. Group DBG: CSD filled with a DBG; group DBG/LV: CSD filled by the combination of DBG and HA in a low-visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…Similarly, HA promotes bone regeneration by influencing cell proliferation and osteogenic differentiation. In a review of the literature, it was found that HA could be positive for the expression of BMP-2 or other osteoprogenitor and osteogenic markers as it provides an ideal environment by virtue of its physicochemical properties (Nickel and Mueller, 2017;Matheus et al, 2020;Cabreira et al, 2021). In this study, the expression of BMP-2 was upregulated at 4 and 8 weeks.…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, HA promotes bone regeneration by influencing cell proliferation and osteogenic differentiation. In a review of the literature, it was found that HA could be positive for the expression of BMP-2 or other osteoprogenitor and osteogenic markers as it provides an ideal environment by virtue of its physicochemical properties (Nickel and Mueller, 2017;Matheus et al, 2020;Cabreira et al, 2021). In this study, the expression of BMP-2 was upregulated at 4 and 8 weeks.…”
Section: Discussionmentioning
confidence: 55%
“…In the groups treated with biomaterial, a significantly higher number of TRAP-positive cells was observed, possibly because of the reduction in the rate of resorption by osteoclasts during repair. Conflicting data are presented in these groups when combined with the greater amount of new bone, suggesting that accelerated resorption of graft granules before 30 days is not beneficial to bone formation, which was confirmed by the percentage of new bone tissue formed lower in the groups treated with clot at the end of the experiment [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Matheus et al, 18 evaluated the potential of different formulations of hyaluronic acid to improve the formation of new bone in critical-sized calvaria defects combined with a deproteinized bovine graft material (DBG), demonstrating that the combination of HA in a high viscosity crosslinking agent with DBG enhances the bone repair process and increases the amount of newly formed bone. These studies show, like the present study, that hyaluronic acid combined with another biomaterial improves the bone regeneration process.…”
Section: Discussionmentioning
confidence: 99%